Morphomolecular Characterization of Serum Nanovesicles From Microbiomes Differentiates Stable and Infarcted Atherosclerotic Patients - Moreno, Camila Rodrigues; Ramires, José Antonio Franchini; Lotufo, Paulo Andrade; Soeiro, Alexandre Matos; Oliveira, Luanda Mara da Silva; Ikegami, Renata Nishiyama; Kawakami, Joyce Tiyeko; Pereira, Jaqueline de Jesus; Reis, Marcia Martins; Higuchi, Maria de Lourdes (Frontiers in Cardiovascular Medicine, 2021)
Microbial communities are considered decisive for maintaining a healthy situation or for determining diseases. Acute myocardial infarction (AMI) is an important complication of atherosclerosis caused by the rupture of atheroma plaques containing proinflammatory cytokines, reactive oxygen species, oxidized low-density lipoproteins (oxLDL), damaged proteins, lipids, and DNA, a microenvironment compatible with a pathogenic microbial community. Previously, we found that archaeal DNA-positive infectious microvesicles (iMVs) were detected in vulnerable plaques and in the sera of Chagas disease patients with heart failure. Now, we characterize and quantify the levels of serum microbiome extracellular vesicles through their size and content using morphomolecular techniques to differentiate clinical outcomes in coronary artery disease (CAD). We detected increased numbers of large iMVs (0.8–1.34 nm) with highly negative surface charge that were positive for archaeal DNA, Mycoplasma pneumoniae antigens and MMP9 in the sera of severe AMI patients, strongly favoring our hypothesis that pathogenic archaea may play a role in the worst outcomes of atherosclerosis. The highest numbers of EVs <100 nm (exosomes) and MVs from 100 to 200 nm in the stable atherosclerotic and control healthy groups compared with the AMI groups were indicative that these EVs are protective, entrapping and degrading infectious antigens and active MMP9 and protect against the development of plaque rupture. Conclusion: A microbiome with pathogenic archaea is associated with high numbers of serum iMVs in AMI with the worst prognosis. This pioneering work demonstrates that the morphomolecular characterization and quantification of iEVs in serum may constitute a promising serum prognostic biomarker in CAD.